Metacognitive Skills in STEM Integrated Discovery Learning Models for Kinetic Gas Theory in High School - Shinta Dewi Susanti; Lia Yuliati; Endang Purwaningsih (Universitas Lambung Mangkurat, 2024)
Metacognitive skills are an important component supporting mastery of concepts in studying physics. This research aims to describe students' metacognitive skills through STEM-integrated discovery learning on kinetic gas theory material at SMAN 1 Dolopo. This research uses the One-Group Pretest-Posttest Design method, where in this design, one experimental group is selected to measure students' metacognitive abilities. The research on the kinetic theory of gas metrics was carried out in class XI Merdeka 4. The research took place in the odd semester of 2022-2023. The results of students' metacognitive skills show an increase in every metacognitive aspect, namely planning skills. The increase occurred in every meta-cognitive aspect, namely planning skills, which were originally 66.4 to 73.7. Monitoring skills, which previously received a score of 60.4, also changed to 73. Evaluating skills possessed by students also changed, from 64.4 to 67.4. Significant increases occurred from the pretest to the posttest, especially in the monitoring skills category. From the table, it is known that the increase occurred from the moderately developed to the developed category. Based on the research and discussion results, the metacognitive skills of class XI Merdeka 4 students are included in the developing category after receiving STEM-integrated discovery learning. This is in line with research that states that the inquiry learning model, including the discovery learning model, positively affects students' metacognition in learning. High-performing students may have better metacognitive skills than low-performing students. High-performing students may have better metacognitive skills than low-performing students.